Gênese, lugar e perspectivas da vigilância socioassistencial: estudos no campo da política de assistência social nos municípios de Belém e Ananindeua - TORRES, Amiraldo Lima (Universidade Federal do Pará, 2017)
This study aims at seeking the determinants of the emergence of the place of Social Assistance Surveillance in terms of National Social Assistance Policy and the municipalities of Belém and Ananindeua. The work uses the critical dialectic method, with methodology based on bibliographical research, documentary and on the field. In the textual body makes a small search on Social Policy and Social Service then, treat the Surveillance of social assistance and their inspirations, interpretations and role in Social Assistance. The research makes the analysis of national conferences, registration and municipal Social assistance system. Following, the speech of actors, social control management and contributions from Federal and State Government agents, aim to analyze the understanding and structuring of Surveillance of Social Assistance, in addition to the perception of the concepts of vulnerability, risk and territory. The search displays the principle of determinants, tensioned by focusing discussions of the Social State and law. In Genesis, we draw a timeline, with determinations of health, assistance and the World Bank. Regarding the place given to Social Assistance Surveillance seats on provided management function and not as a function of Social Assistance, occupying the place of action means and not an end as well, there is no standardization of composition of the teams according to size of municipality and tending to be operationalized by teams not too wide or double and/or just a technician in most municipalities. The work also concluded that Social Assistance Surveillance if structure with thin participation of municipal managers and social control, represents a limit to a conception of Social Function and locus of information organization on the territorial reality and the cities.